Идентификация параметров задач термоупругости составного цилиндра при нестационарном поле температур - Сергиенко, И.В.; Дейнека, В.С. (Проблемы управления и информатики, 2009)
Представлено явні вирази градієнтів функціоналів-нев’язок для ідентифікації градієнтними методами різних параметрів задач термопружного деформування складеного кругового циліндра. Explicit expressions of gradients of functionals-discrepancies for identification of different parameters of the problems of compound circular cylinder thermoelastic deformation by gradient methods are represented.